Sustainable heavy metal immobilization in contaminated soils using plant-derived urease-driven biomineralization - Wangqing Xu; Junjie Zheng; Hanjiang Lai; Mingjuan Cui (PLoS ONE, 2025)
Soil contamination by heavy metals presents substantial ecological and geotechnical risks, thereby demanding sustainable remediation strategies. Conventional approaches, including chemical stabilization and microbial-induced carbonate precipitation (MICP), are limited by high costs, ecological disturbances, and sensitivity to environmental stressors. A plant-derived urease-driven enzyme-induced carbonate precipitation (EICP) system was evaluated for immobilizing cadmium (Cd2⁺), lead (Pb2⁺), and zinc (Zn2⁺) in contaminated soils. Systematic screening revealed that jack bean and watermelon seed ureases are optimal catalysts for heavy metal sequestration, achieving efficiencies of 87.3% for Cd2 ⁺ , 91.5% for Pb2 ⁺ , and 76.4% for Zn2 ⁺ . These high efficiencies are attributed to their catalytic specificity and the retained enzymatic activity under environmental stress. Critical process parameters were fine-tuned through iterative experimentation, maintaining a urea-CaCl₂ reaction stoichiometry of 1.5:1 molar ratio and calibrating the enzyme dosage to 1.2 U/g of soil matrix. This optimized operational range effectively promoted carbonate mineralization while preserving essential soil hydraulic properties, as evidenced by sustained permeability exceeding 10 ⁻ ⁵ cm/s throughout precipitation cycles. Durability assessments under simulated acid rain and freeze-thaw cycles demonstrated 82.5% retention of Cd2⁺ and 92.7% retention of unconfined compressive strength, outperforming conventional lime and MICP treatments. X-ray diffraction analysis confirmed the presence of stable crystalline phases. Field validation confirmed that the EICP protocol can be feasibly scaled to real-world sites with operational costs averaging $52 per cubic meter, representing a 61% reduction compared to microbial-based treatments. This plant-based EICP approach offers a scalable and cost-effective solution for ecological restoration and geotechnical stabilization in contaminated soils, demonstrating significant potential for sustainable environmental management.